Author Correction: The structure of the ubiquitin-like modifier FAT10 reveals an alternative targeting mechanism for proteasomal degradation - Annette Aichem (Nature Portfolio, 2018)
The original version of the Supplementary Information associated with this Article inadvertently omitted Supplementary Table 3. The HTML version of the Article has been updated to include a corrected version of the Supplementary Information.